Peran Kualitas Pelayanan Dalam Memediasi Pengaruh Disiplin Kerja Dan Fasilitas Terhadap Kepuasan Masyarakat : Studi Kasus Pada Dinas Kependudukan Dan Catatan Sipil Tebing Tinggi - Arseto, Dedy Dwi; Sahbania, Aulia (Management And Business Progress, 2023)
This study aims to determine the role of service quality in mediating the effect of work discipline and facilities on community satisfaction (a case study at the Tebing Tinggi Department of Population and Civil Registration). The research method used is a quantitative method using SPSS version 25.00. The data collected from the results of questionnaires distributed to the people of the city of Tebing Tinggi were 96 respondents. The analytical method used in this study is to use an instrument test, namely the validity and reliability test. The classical assumption test is normality test, multicolonearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination (R2) analysis, hypothesis testing, namely T test and path analysis. The results of SPSS in this study are the work discipline variable (X1) that affects the service quality variable (Z), the facility variable (X2) has no effect on the service quality variable (Z), the work discipline variable (X1) has an effect on community satisfaction (Y ), the facility variable (X2) has no effect on community satisfaction (Y), the service quality variable (Z) has no effect on community satisfaction (Y) and path analysis shows service quality (Z) cannot mediate the relationship of work discipline (X1) to satisfaction community (Y), and service quality (Z) can mediate the relationship of facilities (X2) to community satisfaction (Y).